Magnitudes of basic slag on iron dynamics in Two acid sulfate soils during 30-months of incubation under various moisture regimes (Dhaka University Journal of Biological Sciences, 2023)
The magnitudes of basic slag (BS) at 0, 10, 20 and 30 t ha-1 on iron dynamics in two acid sulfate soils (ASSs) under moisture at field capacity, saturated condition and wetting-drying cycle were studied during 30 months of incubation (25-30 0C). The impacts of BS in Sarisabari ASS were almost similar as those obtained in Purbapukuria ASS under various treatments, but the increments of pHs in Sarisabari ASS were not as pronounced as those observed in Purbapukuria ASS. The pH values were increased by about 1.0, 1.5 and 1.2 units in Sarisabari and 2.0, 1.7 and 1.5 in Purbapukuria ASSs, those received BS30 at field capacity, saturated condition and wetting-drying cycle, respectively and followed by BS20 > BS10 treatments. The contents of basic cations in the studiedASSswere low to medium, while acidic cations were very high in relation to the amounts found in the ASSs elsewhere. Magnesium contents were about 2 to 3 -folds than those of Ca but Fe contents were very high. The application of basic slag in the ASSs was found to reduce the acidity problems noticeably and decreased the Fe contents remarkably. Neutralization of acidity by BS30 at saturation moisture level was determined to be the best for both the ASSs followed by moisture at field capacity and wetting-drying cycle. The soil pH was found to have strong positive relationship with time, while the Fe contents showed strong negative relationship with the corresponding pHs of the ASSs. These indicate that the amelioration of ASSs by the application of BS is a sustainable reclamation and improvement measures regarding Fe toxicity of the soils.Dhaka Univ. J. Biol. Sci. 32(1): 107-118 2023 (January)